Experimental and kinetic studies of ignition processes of the methane–n-heptane mixtures. (1st January 2019) - Liang, Junjie; Zhang, Zunhua; Li, Gesheng; Wan, Qi; Xu, Li; Fan, Shidong
Abstract: Ignition delay times of methane– n -heptane mixtures at different methane contents were determined at various initial temperatures through a shock tube setup. Based on comparisons between the experimental and modeled values of ignition delay times of methane– n -heptane mixtures, the applicability of two reaction schemes to the simulation of the zero-dimensional constant-volume adiabatic ignition processes of the mixtures at the present conditions was validated. Then mole fractions of the species and main radicals involved and rates of the main elementary reactions for the formation and consumption of methane and n -heptane in the ignition processes were analyzed. The results show that a nonlinear relationship exists between the ignition delay time of methane– n -heptane mixtures and the methane content. The ignition delay time of methane will change significantly when even a little amount of n -heptane is mixed with methane. It is proved that the two reaction mechanisms studied can predict accurately the ignition delay times of the mixtures under the present initial conditions. Due to the existence of n -heptane, all methane will be reacted early, and the more n -heptane there exists, the earlier all methane is consumed. Different from HO2, CH3 and H2 O2, concentrations of OH, H and O remain low during the ignition period, and only when approaching the ignition time points, their concentrations begin to rise. The formation and consumption reactions for methane occur mainly near the ignition time points. For n -heptane, it is consumed in a short time, and the decomposition reactions prevail at the start of the ignition period. Then the reactions between n -heptane and the radicals take the dominant positions. Compared to methane, n -heptane has a stronger competitiveness for the radicals.